Understanding Early Modern Beer: An Interdisciplinary Approach - Flavin, Susan; meltonville, Marc; Taverner, Charlie; Reid, Joshua; Lawrence, Stephen; Belloch-Molina, Carlos; Morrissey, john (My University, 2023)
Beer was a staple of early modern diets across northern Europe and the Atlantic World. While its profound social, economic, and cultural significance is well established, little is known about the nature and quality of the drink itself, particularly its nutritional characteristics. Until now, attempts to estimate calorie and alcohol content have been monodisciplinary in approach, involving either theoretical calculations based on grain content, or a rough approximation with modern equivalents. Using sixteenth-century Ireland as a case-study, this article describes an interdisciplinary approach to the problem of early modern beer. Exploiting a rich seam of unpublished archival material, the project recreates an early modern beer, using the most appropriate ingredients, equipment, and processes possible. Scientific analysis of the finished drink offers new perspectives on beer as a dietary staple. The project is a model for integrating practical or experimental approaches into mainstream historical study, and the practice of radical interdisciplinarity. It represents the most comprehensive effort to recreate an historic beer in any context to date, bringing together historians, experimental archaeologists, agronomists, microbiologists, brewing scientists, craftworkers, farmers, and maltsters to tackle problematic questions about the past.
PUBLISHED
Keywords: Food history; early modern history; Archaeology; Early modern ireland, colonial communities; History of Medicine; Irish History; Irish Social History; Urban and economic history; environmental history